Small Firms and Superfund: Assessing the Impact - Jeffrey E. Sohl; William E. Wetzel (Journal of Small Business Finance, 1994)
While all firms experience varying degrees of difficulty in complying with environmental regulations, small firms have their own set of special problems in dealing with environmental compliance. The lack of legal and engineering staffs, the management structure, and a high cost per unit of production to comply with environmental regulations implies a diversion of a small firm's limited resources to formulating a cost effective response to the rapidly changing landscape of environmental regulations. The cornerstone of the shifting focus towards hazardous waste regulation, in terms of both actual and potential impacts, is the Comprehensive Environmental Response, Compensation, and Liability Act, commonly referred to as Superfund. Given the unique liability features of Superfund, the objective of this research is to assess the impact of Superfund liability on the ability of small firms to raise capital, invest in plant and equipment, and to continue their role as the principal job generating segment of the U.S. economy.
Keywords: Q21; L25; Q28; 650; Small Firms; Small Business; Superfund